Fatty acid synthase as a feasible biomarker for triple negative breast cancer stem cell subpopulation cultured on electrospun scaffolds. (September 2021) - Rabionet, Marc; Polonio-Alcalá, Emma; Relat, Joana; Yeste, Marc; Sims-Mourtada, Jennifer; Kloxin, April M.; Planas, Marta; Feliu, Lidia; Ciurana, Joaquim; Puig, Teresa
Abstract: There is no targeted therapy for triple negative breast cancer (TNBC), which presents an aggressive profile and poor prognosis. Recent studies noticed the feasibility of breast cancer stem cells (BCSCs), a small population responsible for tumor initiation and relapse, to become a novel target for TNBC treatments. However, new cell culture supports need to be standardized since traditional two-dimensional (2D) surfaces do not maintain the stemness state of cells. Hence, three-dimensional (3D) scaffolds represent an alternative to study in vitro cell behavior without inducing cell differentiation. In this work, electrospun polycaprolactone scaffolds were used to enrich BCSC subpopulation of MDA-MB-231 and MDA-MB-468 TNBC cells, confirmed by the upregulation of several stemness markers and the existence of an epithelial-to-mesenchymal transition within 3D culture. Moreover, 3D-cultured cells displayed a shift from MAPK to PI3K/AKT/mTOR signaling pathways, accompanied by an enhanced EGFR and HER2 activation, especially at early cell culture times. Lastly, the fatty acid synthase (FASN), a lipogenic enzyme overexpressed in several carcinomas, was found to be hyperactivated in stemness-enriched samples. Its pharmacological inhibition led to stemness diminishment, overcoming the BCSC expansion achieved in 3D culture. Therefore, FASN may represent a novel target for BCSC niche in TNBC samples. Graphical abstract: Image 1 Highlights: Polycaprolactone scaffolds provide a softer 3D alternative to traditional cell culture. Scaffolds expand the triple negative breast cancer stem cell niche. Fatty Acid Synthase (FASN) is hyperactivated in scaffold-cultured cells. FASN inhibition overcomes the stemness expansion achieved in 3D culture.